2009
DOI: 10.1007/s11709-009-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of compacted clay-concrete interface

Abstract: Tests of interface between compacted clay and concrete were conducted systematically using interface simple shear test apparatus. The samples, having same dry density with different water content ratio, were prepared. Two types of concrete with different surface roughness, i. e., relatively smooth and relatively rough surface roughness, were also prepared. The main objectives of this paper are to show the effect of water content, normal stress and rough surface on the shear stress-shear displacement relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…An alternative approach was used for identifying parameters K 0 , U 0 1 , U 0 2 , C c , and C r , which are unavailable from the literature. The value of was estimated based on [45] or can be obtained through a back analysis of direct shear test results [31,[46][47][48][49], ranging from 0.1% to 2% for various soil types. C c and C r were estimated using the empirical formulae reported by Wu et al [50] as follows:…”
Section: Case Studymentioning
confidence: 99%
“…An alternative approach was used for identifying parameters K 0 , U 0 1 , U 0 2 , C c , and C r , which are unavailable from the literature. The value of was estimated based on [45] or can be obtained through a back analysis of direct shear test results [31,[46][47][48][49], ranging from 0.1% to 2% for various soil types. C c and C r were estimated using the empirical formulae reported by Wu et al [50] as follows:…”
Section: Case Studymentioning
confidence: 99%
“…Following the work of Potyondy [8], who studied the interface between soil and various construction materials, many scholars have studied the characteristics of the soil-structure interface . These studies included apparatus modifications and new test methods [9][10][11], which were used to investigate the influence of surface properties on the traditional soil-structure interface (including soil-concrete, soil-steel, and soil-cement grout interfaces) [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]33,34], the interfaces between new materials (including ice-soil and soil-geogrid interfaces) [26][27][28][29][30][31][32], and the exterior load conditions (stress history, monotonic load, or cyclic load condition) [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Chen [21] conducted a series of laboratory large-scale direct shear tests using different types of red clay-concrete interfaces and the surface roughness is found to have a remarkable effect on the interfacial shear strength and shear behavior, which is that the shear strength increases with increased surface roughness. Shakir and Zhu [24] carried out direct shear tests to study the effects of water content and surface roughness on the shear stress-shear displacement relationship of a clay-concrete interface, wherein they found that the interfacial shear sliding dominated the interfacial shear displacement behavior for both relatively rough and smooth interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results showed that at a given applied vertical stress level, the major parameters which controlling the interface shear strength behaviour are particles shape and surface roughness. Recently, the influence of surface roughness on the shear strength behaviour of an interface between silty sand and a cement grout surface by means of direct shear apparatus is investigated by Chu and Yin [16]. Their results indicated that the soil-interface shearing resistance depends primarily on the surface roughness, water content of soil, and magnitude of the applied stress.…”
Section: Introductionmentioning
confidence: 99%